Geology in relation to the ecological system in Peru - Tumialán De La Cruz, Pedro Hugo (2004)
The ecological system in Peru is mainly related to geological features, these ecological systems are located mainly in Quaternary soils. The ecological system is exposed in the Quaternary soil on the slopes of the Cordillera of the Peruvian Andes between the levels of 800 to 3600 masl, between the levels of 3600 to 6000 masl and in the Quaternary soils at the bottom of the valleys of Peru between heights from 0 to 6000 masl. The ecological systems in the Cordillera of the Peruvian Andes undergo an active action due to the effect of external geodynamics such as the huaycos, landslides, landslides, creeps, settlements, sand liquefactions and sand migrations due to the wind effect. The internal geodynamics, represented by the earthquakes, affect the ecological systems in Peru; earthquakes occurred, occur and will occur in Peru because it is located near the convergence tectonic plates (plates of Nazca and South America). The mining activity affects the ecological system in the places where the deposits are located in their exploration, exploitation and abandonment phases of mining operations and in the different types of deposits in Peru, such as copper porphyry, in the disseminated deposits of low grade gold, in the philian silver, gold and polymetallic mountain range type deposits, in the eskarn type, in mantle-type mineralized structures, among other types of additional deposits in the Peruvian territory, where there is great activity in defense of the ecological system and in the improvement of the environment.